We are water protectors - Lindstrom, Carole, 1964-; Goade, Michaela (New York : Roaring Brook Press, 2020)
When a black snake threatens to destroy the Earth and poison her people's water, one young water protector takes a stand to defend Earth's most sacred resource. Inspired by the many indigenous-led movements across North America, this bold and lyrical picture book issues an urgent rallying cry to safeguard the Earth's water from harm and corruption.
Includes bibliographical references.
Caldecott Medal, 2021.
Keywords: Water conservation -- Juvenile fiction